Olasz repülő által ledobva (a mieink által nagy gonddal elkobozva) - Samu, Botond Gergő (Per Aspera ad Astra, 2018)
On the 100th anniversary of the Great War several exhibitions, many literature has been brought to light on several themes and genres. Thanks to the expanding field of interest, the research of the First World War propaganda does not focus on the Western Front only. This monograph tries to introduce the aerial propaganda leaflets of the Italian Front and shows some interesting examples of them. These leaflets can be found in the National Széchényi Library’s onetime First World War Collection, founded on September 1914. The two opposing forces (Austria-Hungary and Italy) faced variant problems and they had to solve them different ways. On the Italian side, the propagandists tried to undermine a multicultural and multilingual empire, creating an enemy, so they blamed the Germans – even if they were Prussians or Austrians – forcing the other nationalities to fight this aimless war for the German’s sake. On the other side, the Austro-Hungarian propaganda machine denounced the Italian government as traitors and they tried to convience the lower classes that their war is pointless and unjust, and they have to pay with their own blood for the madness of their politicians and high command. Each side also tried to find a common ground – historical or cultural – to prove each other that they should not be enemies. In this level of the war they also used graphic materials, like caricatures and other drawings, basically small placards, thrown on the enemy’s trenches, or even photographs of the ’happy life’ in the camps settled for the prisoners of war. The collection also keeps some interesting primary documents on the flight of the Italian poet, Gabriele D’Annunzio over Wien (Volo su Vienna) that reveals the mindset of the Austrian High Command and government right after the act. Photo: National Széchényi Library